Nutritional Interventions May Improve Outcomes of Patients Operated on for Diabetic Foot Infections: A Single-Center Case-Control Study - Ilker Uçkay; Vinoth Yogarasa; Felix W. A. Waibel; Annette Seiler-Bänziger; Maja Kuhn; Margrit Sahli; Martin C. Berli; Benjamin A. Lipsky; Madlaina Schöni (Journal of Diabetes Research)
Aim. While a patient’s nutritional status is known to generally have a role in postoperative wound healing, there is little information on its role as therapy in the multifaceted problem of diabetic foot infections (DFIs). Methods. We assessed this issue by conducting a retrospective case-control cohort study using a multivariate Cox regression model. The nutrition status of the DFI patients was assessed by professional nutritionists, who also orchestrated the nutritional intervention (counselling, composition of the intrahospital food) during hospitalization. Results. Among 1,013 DFI episodes in 586 patients (median age 67 years; 882 with osteomyelitis), 191 (19%) received a professional assessment of their nutrition accompanied by between 1 and 6 nutritional interventions. DFI cases who had professional nutritionists’ interventions had a significantly shorter hospital stay, had shorter antibiotic therapies, and tended to fewer surgical debridements. By multivariate analysis, episodes with low Nutritional Risk Status- (NRS-) Scores 1-3 were associated with significantly lower failure rates after therapy for DFI (Cox regression analysis; hazard ratio 0.2, 95% confidence interval 0.1-0.7). Conclusions. In this retrospective cohort study, DFI episodes with low NRS-Score were associated with lower rates of clinical failure after DFI treatment, while nutritional interventions improved the outcome of DFI. We need prospective interventional trials for this treatment, and these are underway.